Antecedents and Consequences of Supply Chain Integration: Empirical Evidence from a Developing Economy - Jonathan Annan; Nathaniel Boso; John Mensah; Nagbe Sulee Eliza (International Journal of Supply Chain Management, 2016)
The purpose of this study is to investigate the firm resource and external environment drivers and operational performance consequences of supply chain integration. The studys theoretical model is tested on a sample of small and medium-sized firms located in Liberia, a Sub-Sahara African economy that is recovering from several years of civil strife and economic turbulence. Findings from the study suggest that increases in inter-firm networking resource and a high degree of dysfunctional competitive conditions drive greater degree of supply chain integration in Liberia. Additionally, findings indicate that increases in supply chain integration enables firms in Liberia to create superior customer value and boost operational efficiency. We discuss several theoretical and managerial implications from these findings.